Aetiology and Clinical Profile of Giant Left Atrium – An Observational Study - Islam, A K M Monwarul; Majumder, Abdullah AS; Ullah, Mohammad; Rahman, Md Toufiqur; Khalequzzaman, Md; Kabiruzzaman, Md; Ghosh, Sujit Kumar; Rahman, Shovan; Dutta, Bijoy; Azad, Shahriar; et al. (Cardiovascular Journal, 2023)
Background: The predominant cause of giant left atrium (GLA) is rheumatic mitral valvular disease. GLA is commonly defined echocardiographically by measuring the left atrial diameter (LAD). In the context of changing epidemiology of rheumatic heart disease (RHD) globally, and introduction of left atrial volume index (LAVI), the aetiology of GLA and utility of LAVI for defining GLA may be necessary. Methods: The prospective observational study was carried out at a dedicated tertiary care cardiac centre of a developing country to know the aetiology and clinical pattern of GLA over 8 years. GLA was defined echocardiographically as a left atrium (LA) having a diameter ≥80 mm in the left parasternal long-axis view. Follow-up was made over the telephone. Results: Thirty cases of GLA were diagnosed over 8 years from 2013 to 2021. Twenty two were due to rheumatic heart disease (RHD), 7 due to MVP, and 1 due to flail anterior mitral leaflet. Mean LAD was 92.13 ± 16.72 mm, and the mean LAVI was 288.77 ± 134.40 ml/m2. LA thrombus was present in 5 patients, 6 had spontaneous echo contrast (SEC) in LA, 2 had both LA thrombus and SEC. Mean follow-up was 0.99 ± 1.06 years. Out of 15 patients, 5 died, while 10 were alive. Mean survival was 1.8 ± 1.17 years, ranging from less than 1 year to 4 years. Conclusion: RHD continues to be the predominant cause of GLA; however, MVP is also important. The cut-off value of LAVI for defining GLA needs further study. Cardiovasc j 2023; 15(2): 151-158